A case study of an autonomous model between a real and a virtual environment. Issue 1 (3rd April 2021) - Kiss, Gabriella
ABSTRACT: In this short article and accompanying visual essay, I trace the development and implementation of a dialogic site-specific performance in public space. I propose a scenographic method for how to make an empty, abandoned urban public space 'speak': how to choose the site for the performance and how to construct a narrative based on the history of the site. The actual 'set' of the performance, the analogue AR (Augmented Reality) boxes, played with some of the central features of AR technology. These characteristics were, in several respects, consistent with the site-specific performance characteristics presented in the case study. The concept raised in the study builds on the meeting points of these two. The performance created a blurring of real and virtual space through an analogue technique.